1993
DOI: 10.1007/bf01313781
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus reassortants with surface glycoprotein genes of the avian parent viruses: effects of HA and NA gene combinations on virus aggregation

Abstract: A series of 33 human-avian and human-mammalian influenza virus reassortant clones possessing either HA or both HA and NA genes of the avian or mammalian virus was obtained by crosses of A/USSR/90/77 (H1N1) human virus with 5 avian and 1 mammalian influenza virus strains. All of the reassortants possessing NA genes of the H1N1 human parent virus and HA gene of an avian or mammalian parent virus had high values of infectivity/HA activity ratio. Since this feature could result from a limited virion aggregation, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…HA-NA balance can be disturbed by reassortment, transmission to a new host, or treatment with neuraminidase inhibitors. Reassortants expressing avian H3, H4, H10, and H13 subtypes in combination with a human N1 replicated poorly in ECE compared to the parental viruses and were associated with the formation of virus aggregates (32). Serial passaging of these reassortants in ECE resulted in high-yielding nonaggregating variants which contained compensatory mutations in the HA that resulted in decreased affinity for sialic acid containing receptors (33).…”
Section: Discussionmentioning
confidence: 99%
“…HA-NA balance can be disturbed by reassortment, transmission to a new host, or treatment with neuraminidase inhibitors. Reassortants expressing avian H3, H4, H10, and H13 subtypes in combination with a human N1 replicated poorly in ECE compared to the parental viruses and were associated with the formation of virus aggregates (32). Serial passaging of these reassortants in ECE resulted in high-yielding nonaggregating variants which contained compensatory mutations in the HA that resulted in decreased affinity for sialic acid containing receptors (33).…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that sequences in the 3Ј and 5Ј ends of the coding regions within the HA (the present study), NA (6), M (J. Maeda and Y. Kawaoka, unpublished data), and NS (K. Fujii and Y. Kawaoka, unpublished data) vRNAs are required for their efficient incorporation into virions, suggesting that packaging of vRNA segments (most likely as a viral ribonucleoprotein complex) is mediated by RNA-RNA interactions occurring in trans among the viral RNA segments. If so, specific incorporation signals within each segment may restrict reassortment, just as functional interactions (e.g., formation of the polymerase complex [12], HA-NA [12,16,21,32,33,38], and cleavable HA-M2 functional associations [10,11,26,36]) restrict the random reassortment of viral proteins. In this context, it is interesting that in both the 1957 and 1968 pandemics, the PB1, HA, and/or NA genes were introduced into human viruses from avian viruses (17), suggesting a possible link between the HA and PB1 RNA segments.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that an HA/NA functional balance in the recombinant swine virus was one of the factors that contributed to enhanced transmission (4). A balance has also been shown to be important for efficient viral replication in mice and in vitro (4)(5)(6)(7)(8). In swine, an HA/NA balance seems less important for replication and transmission (3,4).…”
mentioning
confidence: 99%